Multicentre, randomised, double-blind, parallel controlled trial to investigate timing of platelet inhibition after coronary artery bypass grafting: TOP-CABG trial study - Yang Wang; Lihua Zhang; Shengshou Hu; Kai Chen; Xin Yuan; Qing Chu; Yingli Zheng (BMJ Open)
Introduction Dual antiplatelet therapy (DAPT), referred to as the combination of aspirin and P2Y12 receptor antagonist (clopidogrel or ticagrelor), potentially improves patency of saphenous vein grafts (SVG) after coronary artery bypass grafting (CABG), while it is further proposed that DAPT potentially increases bleeding risk. Compared with DAPT, de-escalated DAPT (De-DAPT) is an effective antiplatelet strategy for acute coronary syndrome treatment, which significantly reduces the risk of bleeding without increasing the incidence of major adverse cardiovascular events. However, insufficient evidence is available to determine the timing of DAPT after CABG.Methods and analysis The Timing of Platelet Inhibition after Coronary Artery Bypass Grafting (TOP-CABG) is a multicentre, randomized, double-blind, parallel controlled trial, which is conducted in sixteen centres in China. TOP-CABG aims to compare one-year patency rate of SVG between De-DAPT and DAPT and to explore the impact of the two regimens on bleeding events. A total of 2, 300 patients undergoing isolated CABG will be randomized 1:1 to De-DAPT referred to as ticagrelor+aspirin during first three months post-CABG and aspirin+ticagrelor placebo for next nine months or to DAPT group with ticagrelor+aspirin for one year after CABG. Patients, treating physicians and investigators will be blinded to allocation. Patients are evaluated at one, three, six, nine and twelve months post-operatively through an outpatient hospital visit. At one year after CABG, patients are required to take coronary CT angiography (CCTA). The primary efficacy endpoint is occlusion of SVGs and the primary safety endpoint is risk of bleeding episodes (the Bleeding Academic Research Consortium (BARC) classification ≥2) within 1-year after CABG. Secondary outcomes include SVG failure, significant (≥70%) venous or arterial graft stenosis and a series of major adverse cardiovascular events within one year after CABG.Ethics and dissemination The Ethics Committee in Fuwai hospital approved this study (2022-1774). Fifteen centres agreed to participate the TOP-CABG trial, and the study has been approved in these 15 centres by whose ethics committee. The results of the trial will be submitted for publication in a peer-reviewed journal.Trial registration number NCT05380063.